A computer program for translating DNA sequences into protein. - Taylor, P (1986)
This paper describes a comprehensive program for translating one or two DNA sequences into amino acid sequences. Written in FORTRAN, it was designed for maximum flexibility of use and easy maintenance, modification and portability. It has full comments throughout.